Changes in practices & incentives promote CSA and zero deforestation supply chains - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Root Capital designed and began fundraising for 105 million USD worth of climate action finance for borrowers following CSA and zero deforestation practices. The fund will use climate and environmental metrics from Aclimatar and Terra-i+ web tools to identify high adaptation need and high carbon stock climate action leaders to target for investment.